2006
DOI: 10.1007/s00216-006-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Modì: a new mobile instrument for in situ double-pulse LIBS analysis

Abstract: Laser-induced breakdown spectroscopy (LIBS) is a promising technique for in situ elemental analysis. A new mobile instrument for LIBS analysis, developed in a collaboration between Marwan Technology s.r.l. and the Applied Laser Spectroscopy Laboratory in Pisa, is presented, and some applications of it and results from it are outlined. The innovative experimental set-up, based on the use of two suitably retarded laser pulses and a standardless analysis procedure, which overcomes problems related to matrix effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 18 publications
0
47
0
1
Order By: Relevance
“…This lens is mounted on an X, Y translation stage that allows the collection of the light from different regions of the plasma along the direction of plume expansion with a precision better than 0.5 mm, so that the temporal evolution of the ablated plume may be observed without the necessity to utilize for this purpose an ICCD detector. A simple and relatively cheap CCD detector is more convenient for routine spectrochemical practice [36,37] and reduces the total price of a portable LIBS system [38]. In our experiments, to reduce the background caused by continuum radiation, a suitable delay from the laser pulse (depending on the material) is chosen to optimize the spectra obtained.…”
Section: Methodsmentioning
confidence: 99%
“…This lens is mounted on an X, Y translation stage that allows the collection of the light from different regions of the plasma along the direction of plume expansion with a precision better than 0.5 mm, so that the temporal evolution of the ablated plume may be observed without the necessity to utilize for this purpose an ICCD detector. A simple and relatively cheap CCD detector is more convenient for routine spectrochemical practice [36,37] and reduces the total price of a portable LIBS system [38]. In our experiments, to reduce the background caused by continuum radiation, a suitable delay from the laser pulse (depending on the material) is chosen to optimize the spectra obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Laser-Induced Breakdown Spectroscopy analysis (Miziolek et al, 2006) was performed using the double pulse MODI' LIBS Instrument (Bertolini et al, 2006). The instrument uses two Nd:YAG lasers at the fundamental wavelength (1064 nm).…”
Section: Libsmentioning
confidence: 99%
“…The instrument was optimized for measurements at 120 m away from the samples and it has been employed, for instance, for the stand-off detection of explosive residues on solid surfaces. 177 Recently, Bertolini et al 178 have reported the development of the first mobile instrument for double-pulse LIBS analysis, named Modì (Mobile Double-pulse Instrument for LIBS analysis). The instrument employed a double-pulse Nd:YAG laser source capable of emitting two collinear laser pulses (1064 nm, 50 to 120 mJ pulse energy, 0 to 60 µs interpulse separation and 10 Hz double-pulse repetition rate), a focusing lens and collecting optics (lens and optical fiber cable), a sample chamber containing a motorized X-Y stage and an optical microscope for precise sample positioning and microanalysis, a computer, and an echelle spectrograph associated with a bi-dimensional ICCD.…”
Section: Mobile Instrumentsmentioning
confidence: 99%